Peer priority based data scheduling algorithm in P2P streaming system - 任浩 Wang Jinlin You Jiali (高技术通讯（英文版）, 2013)
In order to solve the problem that the existing data scheduling algorithm cannot make full use of neighbors＇ bandwidth resources when allocating data request among several senders in the multi- sender based P2P streaming system, a peer priority based scheduling algorithm is proposed. The al- gorithm calculates neighbors＇ priority based on peers＇ historical service evaluation as well as how many wanted data that the neighbor has. The data request allocated to each neighbor is adjusted dy- namically according to the priority when scheduling. Peers with high priority are preferred to allocate more data request. Experiment shows the algorithm can make full use of neighbors＇ bandwidth re- sources to transmit data to reduce server pressure effectively and improve system scalability.